2020
DOI: 10.3390/cancers12020398
|View full text |Cite
|
Sign up to set email alerts
|

PSA and PSA Kinetics Thresholds for the Presence of 68Ga-PSMA-11 PET/CT-Detectable Lesions in Patients with Biochemical Recurrent Prostate Cancer

Abstract: 68Ga-PSMA-11 positron-emission tomography/computed tomography (PET/CT) is commonly used for restaging recurrent prostate cancer (PC) in European clinical practice. The goal of this study is to determine the optimum time for performing these PET/CT scans in a large cohort of patients by identifying the prostate-specific-antigen (PSA) and PSA kinetics thresholds for detecting and localizing recurrent PC. This retrospective analysis includes 581 patients with biochemical recurrence (BC) by definition. The perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
17
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 42 publications
4
17
2
Order By: Relevance
“…In one of our previous studies, we determined an optimal PSA cutoff level of 1.24 ng/mL for distinguishing between positive and negative PSMA PET/CT results for BC patients after primary prostatectomy (P-P) [ 13 ]. In this study, P-P patients in baseline shots, with PSA < 1.24 ng/mL, showed an overall positivity in 34% (24/71), PSMA-avid local metastases in 13% (9/71), and distant metastases in 10% (7/71), compared to 84% (90/107), 29% (31/107), and 22% (24/107) in patients with PSA ≥ 1.24 ng/mL ( p < 0.001) ( Table 5 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In one of our previous studies, we determined an optimal PSA cutoff level of 1.24 ng/mL for distinguishing between positive and negative PSMA PET/CT results for BC patients after primary prostatectomy (P-P) [ 13 ]. In this study, P-P patients in baseline shots, with PSA < 1.24 ng/mL, showed an overall positivity in 34% (24/71), PSMA-avid local metastases in 13% (9/71), and distant metastases in 10% (7/71), compared to 84% (90/107), 29% (31/107), and 22% (24/107) in patients with PSA ≥ 1.24 ng/mL ( p < 0.001) ( Table 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…[ 68 Ga]Ga-PSMA PET/CT imaging has been shown to accurately detect PCa lesions for LNM [ 11 , 12 ]. These characteristics have led to the evolution of PSMA PET/CT as an important diagnostic tool in nuclear medicine [ 7 , 9 , 13 ]. In 130 patients with intermediate to high-risk PCa, a sensitivity of 65.9% and a specificity of 98.9% for LN staging using [ 68 Ga]Ga-PSMA-11 PET/CT was reported by Maurer et al [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hoffman et al [21] and Meredith et al [22] led large retrospective series of 493 and 425 postprostatectomy patients, respectively, imaged with 68 Ga-PSMA-11. In Hoffman et al's [21] review, with a high median PSA value of 2.98 ng/mL, the overall detection rate was 370/493 (75%), with 56 (15%) of the 370 recurrences identified in the prostatic fossa.…”
Section: Fluciclovinementioning
confidence: 99%
“…Table 1 shows a summary of the topics and the papers included for each topic [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. The majority of papers are focused on prostate cancer (PCa) and radiomics.…”
mentioning
confidence: 99%
“…The majority of papers are focused on prostate cancer (PCa) and radiomics. The first topic has continuously gained interest in last years, in particular after the introduction of prostate specific membrane antigen (PSMA)-based radiopharmaceuticals, as extensively reported by Hoffmann et al [ 18 ] in a cohort of more than 580 patients with recurrent PCa, showing that, after radical prostatectomy, PSMA PET/computed tomography (CT) was able to detect the presence of recurrent disease in more than 50% of patients with a PSA level < 1.24 ng/mL. Moreover, Treglia et al [ 24 ], in a meta-analysis, clearly demonstrated the high detection rate of 18F-labeled PSMA also in patients with a PSA levels < 0.5 ng/mL.…”
mentioning
confidence: 99%